Comparative analyses of CTCF and BORIS occupancies uncover two distinct classes of CTCF binding genomic regions. Issue 1 (December 2015) - Pugacheva, Elena; Rivero-Hinojosa, Samuel; Espinoza, Celso; Méndez-Catalá, Claudia; Kang, Sungyun; Suzuki, Teruhiko; Kosaka-Suzuki, Natsuki; Robinson, Susan; Nagarajan, Vijayaraj; Ye, Zhen; Boukaba, Abdelhalim; Rasko, John; et al.
Abstract Background CTCF and BORIS (CTCFL), two paralogous mammalian proteins sharing nearly identical DNA binding domains, are thought to function in a mutually exclusive manner in DNA binding and transcriptional regulation. Results Here we show that these two proteins co-occupy a specific subset of regulatory elements consisting of clustered CTCF binding motifs (termed 2xCTSes). BORIS occupancy at 2xCTSes is largely invariant in BORIS-positive cancer cells, with the genomic pattern recapitulating the germline-specific BORIS binding to chromatin. In contrast to the single-motif CTCF target sites (1xCTSes), the 2xCTS elements are preferentially found at active promoters and enhancers, both in cancer and germ cells. 2xCTSes are also enriched in genomic regions that escape histone to protamine replacement in human and mouse sperm. Depletion of the BORIS gene leads to altered transcription of a large number of genes and the differentiation of K562 cells, while the ectopic expression of this CTCF paralog leads to specific changes in transcription in MCF7 cells. Conclusions We discover two functionally and structurally different classes of CTCF binding regions, 2xCTSes and 1xCTSes, revealed by their predisposition to bind BORIS. We propose that 2xCTSes play key roles in the transcriptional program of cancer and germ cells.